The peculiar boars of Malloy - Crandell, Doug (Northern Illinois University Press, 2010)
This Sherwood Anderson-award winning farcical novel follows two teenage boys living on a farm in rural Indiana. Their father--a diminutive man and the laughingstock of their small town--purchases two boars in an attempt to impress his neighbors and demonstrate, by proxy, his masculinity. The boars, however, turn out to be resolutely gay and deeply committed to each other, setting off a ridiculous chain of events that brings the spotlight and accompanying media circus to Malloy. In the midst of all of the madness is the boysÆ ongoing, and at once heartbreaking and hilarious, quest to find their wayward mother through a series of touching and humorous flashbacks. Disappointed in their pitiful father, the boys cling to an unrealistic fantasy of their mother, who is in actuality a promiscuous drifter. CrandellÆs depiction of the gay boars provides much of the bookÆs humor and, unexpectedly, its moral compass as he weaves significant and subtly articulated themes of animal rights and gay rights. The Peculiar Boars of Malloy captures the best traditions of American satire, while turning the conventions of the coming-of-age novel on its head. CrandellÆs heart and humor will be appreciated by lovers of satire and animals and those readers possessed of a uniquely Midwestern sense of the ridiculous.